Impact of Covid-19 Pandemic on Customer Satisfaction and Business Performance - Yew, Lew Tek; Ling, Lim Hui; Mohd Fuad, Ahmad Azeedi Reza Bin; Akbal Khan, Afra Binti; Ismail, Aimi Aleeya Binti; Mohammad Hazaini, Ainun Adibah Binti; Kee, Daisy Mui Hung (AIBPM Publisher, 2024)
SARS-CoV-2 virus is the pathogenic virus leading to coronavirus illness, Covid-19. The Covid-19 pandemic has instigated significant global shifts, hence prompting considerable changes. As a result of this occurrence, restrictions were introduced to control the spread of the pandemic. Businesses that focus on digitalization instinctively contribute to higher demand for the purchase of products and services utilizing the Internet. The purpose of study is to examine the main impact of Covid-19 pandemic on customer satisfaction and business performance in Malaysia. In order to conduct the research, data collection will be used such as surveys and observational methods. A total of 150 customers and business owners responded to the survey. The results showed many businesses' continuance depend heavily toward customer behaviour, thus most businesses altered their approach especially towards the standards of product, price, promotion and place to fit in and adjust accordingly. Consequently, research for both aspects were done as there are interrelations between each other. Through this research, we view back measures taken by customers and businesses to navigate during tough times